2015
DOI: 10.1155/2015/249308
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Indole-3-Butyric Acid on Clonal Propagation of Swietenia macrophylla through Branch Cutting

Abstract: The study discloses the scopes of clonal propagation Swietenia macrophylla through branch cutting treated with IBA. A total of four hundred cuttings were used with four replications to assess the rooting ability. The study exposed significant (p<0.5) difference of rooted cuttings among the treatments. The highest (62.51%) rooting percent was observed in cutting with 0.4% IBA treatment. In addition, root number and its length per cutting were increased with increasing IBA concentration (p<0.5). The experi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 24 publications
1
8
0
Order By: Relevance
“…Applications of auxin enhanced rooting and root quality in many tree species (Hartmann et al, 2018). IBA at 4000 ppm induced maximum rooting and produce high quality planting stock in Swietenia macrophylla (Azad and Matin, 2015). While for Duranta erecta 5000 ppm was the best for rooting and furthers than that the inhibitory effects on the rooting was apparent (Shiri et al, 2019).…”
Section: Discussionmentioning
confidence: 90%
See 2 more Smart Citations
“…Applications of auxin enhanced rooting and root quality in many tree species (Hartmann et al, 2018). IBA at 4000 ppm induced maximum rooting and produce high quality planting stock in Swietenia macrophylla (Azad and Matin, 2015). While for Duranta erecta 5000 ppm was the best for rooting and furthers than that the inhibitory effects on the rooting was apparent (Shiri et al, 2019).…”
Section: Discussionmentioning
confidence: 90%
“…The use of cuttings from stems, leaves, roots or terminal buds is considered as the most commonly applied technique due to its practicability and simplicity. It is well known that the success of rooting of woody stem cuttings, in the majority of ornamental plants, depends mainly on the physiological stage of the mother plant, the time of planting of the cutting (Hartmann et al, 2018) and the type of growth regulators used (Azad and Matin, 2015;Azad et al, 2016, Singh andRawat, 2017). The prevailing environmental conditions in the nursery i.e., light, temperature and humidity play an important role in rooting and succeeding growth and development of cuttings (Hartmann et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In 2011, Raji and Osman [13] showed that hormonal factors greatly influence the adventitious rooting in Stevia rebaudiana, a commercially important sweetening medicinal herb and higher concentration (2.3 mM) of IBA induces maximum number of roots within short time. In another study, Azad and Matin [14] concluded that the use of 0.4% IBA for rooting in juvenile leafy branch cutting of Swietenia macrophylla would be effective for mass propagation. Yan et al [12] investigated significant role of NAA in the adventitious rooting in Hemarthria compressa.…”
Section: Introductionmentioning
confidence: 99%
“…The cuttings of S. album rooted well in the present study ( Figure 01). Rooting percent was varied 1.32fold (70.1 -92.6%); average root number per cutting, 3.8-fold (5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19); and average root length, 3.1-fold (3.1-9.6 cm) among the various IBA treatments. The highest rooting percent was observed in 0.8% IBA concentration (T3) and lowest rooting percent was observed in control (T0).…”
Section: Rooting Ability Of Cuttingsmentioning
confidence: 99%